(untitled) (The Review of Diabetic Studies, 2024)
Background: Healthcare-associated infections (HAIs), particularly procedure-related infections (PRIs) from nursing procedures like catheterization and wound care, affect 4-6% of acute care patients, leading to prolonged stays, morbidity, and costs exceeding 28-45 billion annually in the U.S. Common PRIs include catheter-associated urinary tract infections (CAUTIs) at 1-4 per 1000 catheter-days and central line-associated bloodstream infections (CLABSIs) at 1-5 per 1000 line-days, driven by biofilms, skin flora migration, and aseptic lapses. This review synthesizes evidence on nursing-centric prevention amid rising community and ambulatory risks.​ Methods: A narrative synthesis of epidemiological data, clinical guidelines (CDC, WHO, ECDC), and studies on PRIs in catheterization, wound care, injections, and enteral feeding was conducted, drawing from global prevalence surveys, NHSN criteria, and prevention bundles. Pathogenesis, risk factors, and innovations like antiseptic dressings and AI surveillance were analyzed for nursing applicability.​ Results: PRIs cause 10-20% excess morbidity, with CAUTIs at 23-25% of HAIs and CLABSIs mortality at 12-25%; bundles reduce rates by 40-70% via chlorhexidine antisepsis, sterile barriers, and daily audits. Wound care SSIs occur in 2-5% of cases, mitigated by pressure offloading and silver dressings; emerging nanotechnology and tele-nursing cut colonization by up to 90%. Nurse-led education boosts compliance by 50%.​ Conclusions: Targeted bundles, stewardship, and innovations empower nurses to achieve 30-55% HAI reductions, bridging procedural gaps for safer outcomes across settings. Standardized global frameworks are essential.​